Pandemic Threats and the Need for New Emergency Public Health Legislation in Canada - Wilson, Kumanan (Longwoods Publishing, 2006)
The 2003 outbreak of Severe Acute Respiratory Syndrome (SARS) exposed serious limitations in Canada’s ability to respond to a public health emergency. Considerable progress has been made since SARS in addressing these limitations, including the creation of the new Public Health Agency of Canada. A remaining contentious question is whether there is a need for new federal emergency public health powers. Approaches to public health problems are best handled through collaborative processes, recognizing the critical importance of the local public health response. Nevertheless, this paper argues that a legislative back-up plan must be available to the federal government in the event that collaborative relationships break down. At the minimum, legislation should give the federal government the authority to have guaranteed access to surveillance data during a public health emergency. The legislation should also consider providing the federal government with the authority to devote the nation’s resources to the management of an emergency at its earliest stages. However, any legislative approach must be combined with the development of appropriate capacity at the national level to ensure that new powers can be adequately utilized and that required funding reaches public health officials at other levels of government.